2017
DOI: 10.1083/jcb.201704044
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of Pax4 in pancreatic δ cells results in β-like cell neogenesis

Abstract: Diabetes can result from the loss or dysfunction of insulin-producing δ cells. Druelle et al. find that ectopic expression of the pancreatic beta cell master gene Pax4 in somatostatin-expressing δ cells triggers an endocrine cell neogenesis process. Importantly, the beta-like cells thereby generated are functional and can partly reverse the consequences of chemically induced diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…An origin of endocrine cells from ductal epithelium was suggested several years ago (44) and reported in a case of partial pancreatectomy (45). Although the significantly reduced percentage of α and δ cells ( Figure 1G) suggests that these islet cell types are a source of β cell neogenesis as reported recently (43,46), additional lineage-tracing studies are necessary to confirm this possibility. Our previous studies also suggest an association between insulin resistance and increased islet neogenesis in pancreas sections from insulin-resistant humans (47).…”
Section: Discussionmentioning
confidence: 51%
“…An origin of endocrine cells from ductal epithelium was suggested several years ago (44) and reported in a case of partial pancreatectomy (45). Although the significantly reduced percentage of α and δ cells ( Figure 1G) suggests that these islet cell types are a source of β cell neogenesis as reported recently (43,46), additional lineage-tracing studies are necessary to confirm this possibility. Our previous studies also suggest an association between insulin resistance and increased islet neogenesis in pancreas sections from insulin-resistant humans (47).…”
Section: Discussionmentioning
confidence: 51%
“…To test this possibility, we transcriptionally profiled BON and QGP cells using a battery of genes involved in pancreatic, pancreatic endocrine, and islet cell differentiation. PAX4 which is crucial for βand δ-cell development, β/δ-cell lineage bifurcation, and conversion of αor δ-cells into functional β-like cells [16] is restricted at later stages to β-cells. We found that the transcript levels for PAX4 are 10-20-fold more abundant in NT-3 cells than in the two permanent cell lines ( Figure 4A).…”
Section: Expression Of Genes Of Immature β-Cells and Lineage-specificmentioning
confidence: 99%
“…It also promotes pancreatic cell lineage. All these findings therefore allow us to conclude that the expression of PAX4 in somatostatin-positive cells promotes their differentiation into β-like cells, apparently through Hhex down-regulation [145].…”
Section: Ectopic Expression Of Pax4mentioning
confidence: 67%
“…It was shown that PAX4 ectopic expression is sufficient for the conversion of δ-cells into functional insulin-producing cells. Mostly, these induced insulin-producing cells were functional and could slightly change the consequences of chemically-induced diabetes [145]. The ectopic expression of PAX4, either in PDX1-positive or PAX6-positive endocrine cells, led to the observation of β-cell characteristics.…”
Section: Ectopic Expression Of Pax4mentioning
confidence: 99%
See 1 more Smart Citation